ENGINEERING EDUCATION FOR INNOVATION ECONOMIC DEVELOPMENT OF CHUVASH REPUBLIC - Vladimir A. Shchedrin (Moscow Polytechnic University, 2016)
The article analyzes the state of engineering education in Chuvash Republic after signing the Bologna Declaration and the introduction of the new FSES VPO of the third generation; proposes measures for the preservation of the basic foundations of national engineering education. The main idea concerns the formation of a modified baccalaureate model including various modulars and profiles with the different education periods. This model should combine the methodological principles of Bologna Declaration and the advantages of Russian engineering education.